The Lotus Flower and White Frangipani: Cosmological Meaning and Esthetic Practices in Balinese Hindu Rites - Ida Bagus Gde Triguna; I Ketut Winantra; I Putu Suweka Oka Sugiharta (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Flowers are central to Balinese Hindu ritual practice, but previous studies have interpreted them mainly as ritual ornaments, symbolic offerings, or aesthetic complements to ceremonial performance. Much less scholarly attention has been paid to their role as embodied aesthetic media at the intersection of sensory perception, religious experience, and cultural meaning. This study addresses that gap by investigating flowers as integrative media in Balinese Hindu ritual, linking materiality, symbolism, ethics, and spirituality. It adopts a qualitative ethnographic approach based on field observations, in-depth interviews with Hindu priests and ritual practitioners, and textual analysis of the Agastya Parwa. The analysis is also informed by Hindu Aesthetics (Triguna, 2025), symbolic anthropology, and ritual studies. The results show that flowers are not merely aesthetic objects but ritual media embodied in four interrelated dimensions: material, ethical, symbolic-cosmological, and spiritual. Together, these dimensions transform sensory experience into sacred experience. The study reveals the distinctive symbolic roles of ritual flowers, including the lotus (tunjung) as a cosmological symbol of purity and cosmic order, and the white frangipani (Plumeria alba) as an aesthetic conduit of everyday devotion and cultural continuity. Based on these findings, this article proposes the Balinese Hindu Ritual Aesthetics Model, which approaches ritual aesthetics as a holistic religious experience constructed through the interaction of material objects, embodied practice, symbolic meaning, and spiritual consciousness. This model contributes to debates in the anthropology of religion, material religion, ritual studies, and embodied aesthetics by showing that flowers are shared cultural media through which religious values, cultural memory, and cultural resilience are continually reproduced in Balinese Hindu society.